Disability and religious diversity : cross-cultural and interreligious perspectives - Schumm, Darla Y. (Darla Yvonne); Stoltzfus, Michael, 1965- (New York : Palgrave Macmillan, 2011)
"This edited collection of essays critically examines how diverse religions of the world represent, understand, theologize, theorize and respond to disability and/or chronic illness. Contributors employ a wide variety of methodological approaches including ethnography, historical, cultural, or textual analysis, personal narrative, and theological/philosophical investigation. "--
"This edited collection critically examines how diverse religions of the world represent and respond to disability and/or chronic illness. Contributors incorporate literature and theoretical analysis from the field of disability studies resulting in a comparative text reflecting multicultural, interdisciplinary and inter-religious attitudes and perspectives. The book is appealing to a broad readership including members of the disabled community, scholars and students from the disciplines of religious studies, disability studies and cultural studies, social service and healthcare professionals, and religious practitioners from distinctive traditions. Multiple contributors approach their writing from the perspective of living with some form of disability or chronic illness"--
Machine generated contents note: -- Section One: Religion, Narrative Identity and Disability * Performance of Muslim Daily Prayer by Physically Disabled Practitioners -- Arseli Dokumaci * Since Feathers Have Grown on My Body: Madness, Art, and Healing in Celtic Reconstructionist Spirituality -- Erynn Rowman Laurie * Whatever the Sacrifice: Illness and Authority in the Baha'i Faith -- Priscilla Gilman * Stations of Victoria & Rosalina's Broken Bread -- Aimee Burke Valeras * Section Two: Religion, Accessibility and Disability * Disabled Rites: Ritual and Disability in Wicca -- Jo Pearson * A Secular Case for Religious Inclusion of Individuals with Intellectual Disabilities -- Jeff McNair & Abigail Schindler * Health and Disability Care in Native American & Alaska Native Communities -- Lavonna Lea Lovern * Section Three: Inter-Religious and Cross-Cultural Comparisons of Disability * Native American Concepts Involving Human Differences -- Lavonna Lea Lovern * Chronic Illness and Disability: Paradigms of Suffering and Healing in Buddhism and Christianity -- Michael Stoltzfus & Darla Schumm * Disability, Agency and Engagement: Three Wisdom Traditions Call to be Radically Available -- Lynne Bejoian, Molly Quinn & Maysaa Bazna * Best Practices for Faith-Based Organizations Working With Deaf Communities in Developing Countries -- Amy Wilson & Kirk VanGilder.
Includes bibliographical references and index.
Keywords: Disabilities -- Religious aspects; Chronic diseases -- Religious aspects; Human body -- Religious aspects